2019
DOI: 10.3390/pr7100709
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Enhanced Primary Sludge as an Anaerobic Co-Digestion Additive for Biogas Production from Food Waste

Abstract: In order to overcome process instability and buffer deficiency in the anaerobic digestion of mono food waste (FW), chemically enhanced primary sludge (CEPS) was selected as a co-substrate for FW treatment. In this study, batch tests were conducted to study the effects of CEPS/FW ratios on anaerobic co-digestion (coAD) performances. Both soluble chemical oxygen demand (SCOD) and protease activity were decreased, with the CEPS/FW mass ratio increasing from 0:5 to 5:0. However, it was also found that the accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…A further increase in the overall efficiency was observed in a later study of Chakraborty et al [18] who added lime for improving the alkalinity of tested substrates and tested even lower FW-to-CEPT ratios. Kang and Liu [19] agreed well with the studies of Obulisamy et al [9] and Chakraborty et al [18], verifying that an increase in CEPT fraction in the substrate favors the production of biomethane and limits problems associated with increased acidogenesis inside the anaerobic digestors. Interestingly, the amount of cumulative methane produced by the 1:4 FW/CEPT mixture, which was about 2750 mL CH 4, at the end of a 20-day anaerobic digestion procedure was almost two-fold higher than the amount produced by the 3:2 FW/CEPT mixture.…”
Section: Food Waste (Fw) Fruit and Vegetable Waste (Fvw) And The Orga...supporting
confidence: 83%
“…A further increase in the overall efficiency was observed in a later study of Chakraborty et al [18] who added lime for improving the alkalinity of tested substrates and tested even lower FW-to-CEPT ratios. Kang and Liu [19] agreed well with the studies of Obulisamy et al [9] and Chakraborty et al [18], verifying that an increase in CEPT fraction in the substrate favors the production of biomethane and limits problems associated with increased acidogenesis inside the anaerobic digestors. Interestingly, the amount of cumulative methane produced by the 1:4 FW/CEPT mixture, which was about 2750 mL CH 4, at the end of a 20-day anaerobic digestion procedure was almost two-fold higher than the amount produced by the 3:2 FW/CEPT mixture.…”
Section: Food Waste (Fw) Fruit and Vegetable Waste (Fvw) And The Orga...supporting
confidence: 83%
“…The pH of fermentation solution was fixed to 7.2 with sodium bicarbonate solution at the start-up period in the ABD reactor, and slightly increased to 7.41 after a short decrease on the second day. The pH decrease was caused by the acidification of food waste in the acidogenesis step, but it turned to a self-adapted range when the acidogenesis and methanogenesis reached a balanced state [6,33]. The same phenomenon was obtained in the control reactor, wherein the pH increased from 7.2 to 7.28 ( Figure 3).…”
Section: Process Stabilitysupporting
confidence: 57%
“…Li et al [ 85 ] reported a 116% increment in methane yield when this co-substrate was added to the digestion of cattle manure. Food wastes and sewage sludge have also been proposed as co-digesting mixtures [ 86 , 87 ]. Another relevant co-substrate widely studied due to its high biogas yield and great capacity for boosting biogas production is crude glycerol derived from the biodiesel production process.…”
Section: Co-digestion To Increase Reactor Productivitymentioning
confidence: 99%